MicroRNA-124 Promotes Singapore Grouper Iridovirus Replication and Negatively Regulates Innate Immune Response - Li, Pin-Hong; Wang, Li-Qun; He, Jia-Yang; Zhu, Xiang-Long; Huang, Wei; Wang, Shao-Wen; Qin, Qi-Wei; Sun, Hong-Yan (Frontiers in Immunology, 2021)
Viral infections seriously affect the health of organisms including humans. Now, more and more researchers believe non-coding RNAs could regulate viral infection. MicroRNAs (miRNAs), one of the members of non-coding RNAs family, play significant roles in cell biological function, disease occurrence and immunotherapy. However, the roles of miRNAs in virus infection and cellular immune respones remains poorly understanding. In this study, based on the established virus-cell infection model, Singapore grouper iridovirus (SGIV)-infected grouper spleen (GS) cells were used in this study, the roles of miR-124 of Epinephelus coioides, an economically mariculture fish in southern China and Southeast Asia in viral infection and host immune responses were investigated. The expression level of E. coioides miR-124 was significantly up-regulated after SGIV infection; and the up-regulated miR-124 could significantly promote the SGIV-induced cytopathic effects (CPE), the viral titer, and the expressions of viral genes. miR-124 could target JNK3/p38α MAPK, dramatically inhibit the activation of NF-κB/AP-1, the transcription of proinflammatory factors, caspase-9/3, and the cellular apoptosis. And the opposite results happens when the expression of miR-124 was inhibited. The results suggest that miR-124 could promote viral replication and negatively regulate host immune response in fish, which furthers our understanding of virus and host immune interactions.